Tetrastichus howardi (Hymenoptera: Eulophidae): First report of parasitism in oxydia vesulia (lepidoptera: Geometridae) - Favoreto, Ana Laura [UNESP]; Pavani, Rafaela Freitas [UNESP]; Ribeiro, Murilo Fonseca [UNESP]; Zanuncio, Antonio José Vinha; Soares, Marcus Alvarenga; Zanuncio, José Cola; Wilcken, Carlos Frederico [UNESP] (FapUNIFESP (SciELO), 2021)
The adaptation of native lepidopteran species to eucalyptus plantations reduces the productivity of this crop in Brazil. Oxydia vesulia Cramer (Lepidoptera: Geometridae) is a secondary pest, frequently reported in eucalyptus plantations with population outbreaks and economic damages. Methods of biological control of this pest may include the use of the exotic pupae endoparasitoid Tetrastichus howardi Olliff (Hymenoptera: Eulophidae), reported as efficient to controlling lepidopteran pests. The parasitism of O. vesulia caterpillars and pupae by T. howardi was evaluated under controlled conditions (25 ± 1 ºC, 60 ± 20% humidity and 12:12 h L:D). Each O. vesulia caterpillar or pupae was individually placed in a flat-bottom tube with 10 and 15 females of T. howardi for 48h, respectively. The parasitoids were removed after that period, the caterpillars were fed and the pupae were maintained until emergence of the parasitoid or formation of pupae and emergence of adults of this pest. The fourth-instar caterpillars of O. vesulia, after the parasitism period, were kept in pots with Eucalyptus urophylla leaves, changed daily until the end of the experiment. A total of 40% of the caterpillars died before the pre-pupae stage, 40% reached the pupae stage and died due to inadequate adult formation and 20% generated moths, but none adult parasitoid emerged from the caterpillars. All pupae of O. vesulia were parasitized and showed emergence of parasitoids. The parasitism of O. vesulia caterpillars and pupae by T. howardi shows the potential of this natural enemy for the integrated management of this defoliator pest in eucalyptus plantations.
Tetrastichus howardi (Hymenoptera: eulophidae): primeiro relato de parasitismo em oxydia vesulia (lepidoptera: geometridae)
Keywords: Biological control; Caterpillar and pupae parasitoid; Eucalyptus